Feto-maternal outcome of placenta previa with or without placenta accreta spectrum in tertiary hospital Dhaka - Siddiquee, Nazma; Roy, Marlin; Majeed, Meherin; Jannat, Farhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Placenta previa, with or without placenta accreta spectrum (PAS), is linked to significant maternal and fetal morbidity and mortality, primarily due to complications like cesarean delivery, severe antepartum/postpartum hemorrhage and preterm birth. The combined military hospital (CMH) Dhaka, with its advanced facilities and sufficient case volume, provides an ideal environment for this research. The main objective was to evaluate the feto-maternal outcomes of placenta previa with or without PAS and develop a management framework to improve these outcomes. Methods: This retrospective study was conducted in the Department of Obstetrics and Gynecology at CMH Dhaka. The study population consisted of 99 pregnant women with placenta previa and PAS admitted between January 2023 and June 2024. Data were collected through a questionnaire, ultrasound reports, operative findings and histological reports. Results: The mean age of participants was 29.59 years. Women with a previous cesarean section had a higher risk of placenta previa (71.71%). Planned cesarean sections were performed at 34-36 weeks of gestation in 70.7% of cases. Emergency LSCS was required in 9 cases due to antepartum hemorrhage (APH), while 88 were elective cesarean sections and 2 were incidental findings during elective LSCS. Intraoperative complications included bladder injury (47 cases) and peripartum hysterectomy (61.61%). Among the newborns, 25 (25.25%) had a birth weight of 1-2 kg and 77 (77.77%) were preterm, with 5 (5.05%) being very low birth weight. APGAR scores<6 at one minute were observed in 14 babies, while 85 babies had scores>6. Conclusions: Placenta previa with or without PAS is strongly associated with serious maternal and fetal complications. Our study aims to formulate management guidelines to improve outcomes for both mother and baby.